The essentials of the new workplace : a guide to the human impact of modern working practices - Holman, David (David J.) (John Wiley & Sons, 2005)
The original hardback edition of The New Workplace examined modern business terms such as total quality management, just-in-time production, e-business, lean manufacturing and teleworking. It explored what these terms really mean and what effect they have in practice - especially their impact on productivity and performance and their social and psychological consequences.